GNG7 as a tumor-suppressor gene in lung adenocarcinoma: implications for prognosis and immune-based therapies - Luo, Kexin; Liu, Meihan; Peng, Zhongqin; Zhao, Haiyang; Li, Guoyi; Cai, Yuanze; Lei, Yumeng; Zhang, Hongpan; Zhao, Yongsheng (Frontiers in Oncology, 2025)
IntroductionLung adenocarcinoma (LUAD) is among the most prevalent and lethal forms of cancer worldwide, largely due to the lack of early symptoms and frequent late-stage diagnosis. G protein γ subunit 7 (GNG7) has been implicated in the regulation of cell proliferation, apoptosis, and migration across various cancers. However, its immunological role in LUAD progression remains poorly understood.MethodsWe analyzed The Cancer Genome Atlas (TCGA) database to assess the relationship between GNG7 expression and clinical outcomes in LUAD. Immune cell infiltration and immune-related gene expression were evaluated in association with GNG7 levels. In vitro functional assays, including proliferation, migration, invasion, and apoptosis assays, were performed following GNG7 overexpression. A prognostic model was constructed based on immune-related genes regulated by GNG7 and validated using the GSE31210 and IMvigor210 cohorts.ResultsLow GNG7 expression was associated with enhanced tumor growth and poor prognosis in LUAD patients. GNG7 expression correlated significantly with immune cell infiltration and key immune regulatory markers. In vitro, GNG7 overexpression suppressed LUAD cell proliferation, migration, and invasion, while promoting apoptosis. The developed GNG7-related immune gene prognostic model effectively predicted both patient prognosis and immunotherapy response.DiscussionOur findings highlight the critical role of GNG7 in LUAD progression and its modulation of the tumor immune microenvironment. GNG7 shows promise as a prognostic biomarker and potential therapeutic target for immune-based LUAD treatment strategies.